Reconstrues Legislation: The Effectiveness of Presidential Veto in Government System in Indonesia Based on the State of The Republic of Indonesia 1945 Constitution - Elwan, La Ode Muhammad (Halu Oleo Law Review, 2018)
In the Indonesian Government System, the president is the supreme authority of the government under the 1945 Constitution of the State of the Republic of Indonesia. After 4 (four) amendments to the 1945 Constitution, the presidential power experienced a shift in function and role as a result of the magnitude of the flow of political interests, so that almost all the power of the president on the authority of legislation in the 1945 Constitution of the 1945 Constitution largely lacked a permanent legal power and formal juridical. We know that the substance of the authority of presidential legislation if based on the presidential system of government does not exist and is not given real space. Consequently, the president as the mandate of the people's sovereignty must be able to control the system of government even though the fact that there is dominance of the legislative institution to the presidential institution together with the cabinet that is the authority of presidential legislation in the constitution of the state 1945 Constitution has no law forces so that the wheel of development does not run normally -target is planned. The hope is that our country's constitution must be able to guarantee the principle of balance of authority and mutual supervision that governs the legislation of the president against the product of the law. Writing methodology based on the literature review contained in books, papers, newspapers, scientific articles, journals, and legislation as the object under study. The results of the study and analysis conclude: (1) The Veto of the President is not effective when reviewed in the constitutional document of the 1945 Constitution of the Republic of Indonesia; (2) The inconsistency of the Presidential Government System of Indonesia with the contents of the articles of the 1945 Constitution of the Republic of Indonesia; (3) it is recommended that the fifth amendment of the 1945 Constitution of the Republic of Indonesia and the revision of Law Number 12 Year 2011 on the Establishment of Legislation to be followed up by MPR RI and the President; (4) The Presidential Regulation in Lieu of Law, according to the authors must be absolutely given to the President without the intervention of the House of Representatives because the President as Head of State and has the Highest Government Authority under the 1945 Constitution between State Institutions.